2001
DOI: 10.1001/archinte.161.20.2481
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Automated Dementia Screening Using a Touch-Tone Telephone

Abstract: Computer-automated telephone screening for early dementia using either informant or direct assessment is feasible. Such systems could provide wide-scale, cost-effective screening, education, and referral services to patients and caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…Alternative communication modes such as videoconferencing and computer-automated or computer-assisted telephone screening, while at an early stage of development, show promise for the future [68][69][70]. Although it might be possible to adapt the MATS to one of these formats, it remains to be seen whether these technologies become widely available, cost-effective, and readily embraced by older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative communication modes such as videoconferencing and computer-automated or computer-assisted telephone screening, while at an early stage of development, show promise for the future [68][69][70]. Although it might be possible to adapt the MATS to one of these formats, it remains to be seen whether these technologies become widely available, cost-effective, and readily embraced by older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies reported results for more than two groups of participants: three included healthy controls, MCI and early dementia, 71,76,86 and two included healthy controls, early dementia and early dementia/MCI combined. 70,74 In total, 10 studies 68,69,71,72,75,76,78,79,85,86 evaluated the use of automated computerised tests to detect MCI alone, seven studies 70,71,74,76,80,81,86 reported results for early dementia, three studies 70,74,77 reported results for combined MCI/early dementia and one study 83 reported results for human immunodeficiency virus (HIV)-associated neurocognitive disorder (HAND).…”
Section: Included Studiesmentioning
confidence: 99%
“…[68][69][70][77][78][79][80]85 The studies were judged to be at high risk for this criterion because a case-control study design was used. Regarding the index test criteria for risk of bias, seven studies 70,71,74,76,78,83,85 were judged to be at unclear risk.…”
Section: Study Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations